2022
DOI: 10.1021/acsomega.2c05142
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of Adsorption Behaviors and Electronic, Optical, and Gas-Sensing Properties of Pure and Pd-Decorated GeS2 Monolayers

Abstract: The extensive applications of two-dimensional (2D) transition metal disulfides in gas sensing prompt us to explore the adsorption, electronic, optical, and gas-sensing properties of the pure and Pd-decorated GeS2 monolayers interacting with NO2, NO, CO2, CO, SO2, NH3, H2S, HCN, HF, CH4, N2, and H2 gases by using first-principles methods. Our results showed that the pure GeS2 monolayer is not appropriate to develop gas sensors. The stability of the Pd-decorated GeS2 (Pd-GeS2) monolayer was determined by binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…The relatively low value of adsorption energy and high adsorption distance between the Cc and the monolayer indicates the predominance of strong physisorption . In the pursuit of developing an efficient sensor, it is often desirable that the interaction should be strong enough to retain the Cc on the substrate surface, i.e., a weak chemisorption is often preferred . Therefore, the surface of the Nb 2 S 2 C monolayer is modified with TM functionalization to attain weak chemisorption of the Cc molecule.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The relatively low value of adsorption energy and high adsorption distance between the Cc and the monolayer indicates the predominance of strong physisorption . In the pursuit of developing an efficient sensor, it is often desirable that the interaction should be strong enough to retain the Cc on the substrate surface, i.e., a weak chemisorption is often preferred . Therefore, the surface of the Nb 2 S 2 C monolayer is modified with TM functionalization to attain weak chemisorption of the Cc molecule.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Earlier studies have reported that the type of molecule can also be distinguished by the differences in the optical properties of the adsorption of various molecules on the same substrate. Here, we will discuss the visible light absorption of doped cases in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…This behavior is due to its excellent electronaccepting/donating behavior when interacting with the substrate and gas. Previous studies 34,59 have reported that the DOS variation of a system before and after adsorption can indicate the type of adsorption. Thus, to further confirm this point, the total density of states (TDOS) and projected density of states (PDOS) are discussed in Figure 5.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…迄今为止, 3 GeS 2 纳米片的各种物理性质已经得到了广泛的研究. Gao 等人研究了 Pd 修饰 GeS 2 单层的吸附 行为及电子、光学和气敏特性 [25]. Ruan 等人研究发现拉伸应变可提高单层 GeS 2 的热电性能 [26] .…”
Section: 引言 最近研究表明 通过堆叠两种或更多不同的二维 ( 2d ) 材料构建范德华异质结 ( Vdwhs )unclassified